2001
DOI: 10.1016/s0006-3495(01)75804-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pyrene Phospholipid/γ-Cyclodextrin Complex

Abstract: Recently, it was demonstrated that gamma-cyclodextrins (gamma-CDs) greatly accelerates transfer of hydrophobic pyrene-labeled and other fluorescent phospholipid derivatives from vesicles to cells in culture (). To understand better the characteristics of this process, we studied the interaction of gamma-CD with pyrene-labeled phosphatidylcholines (PyrPCs) using a variety of physical methods. Either one or both of the acyl chains of PC was labeled with a pyrene moiety (monoPyrPCs and diPyrPCs, respectively), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…Cell viability was not signifi cantly com- decreased at higher me ␤ -CD concentrations. This is not unexpected, because the affi nity of phospholipids for cyclodextrin (relative to that for the bilayer) has been shown to increase with decreasing hydrophobicity ( 9 ). Thus, if the concentration of me ␤ -CD is too high, it binds much of aqueous media presents a major obstacle here.…”
Section: Effects On Cell Growth and Viabilitymentioning
confidence: 88%
“…Cell viability was not signifi cantly com- decreased at higher me ␤ -CD concentrations. This is not unexpected, because the affi nity of phospholipids for cyclodextrin (relative to that for the bilayer) has been shown to increase with decreasing hydrophobicity ( 9 ). Thus, if the concentration of me ␤ -CD is too high, it binds much of aqueous media presents a major obstacle here.…”
Section: Effects On Cell Growth and Viabilitymentioning
confidence: 88%
“…The degree of incorporation diminished nearly exponentially with lipid hydrophobicity (data not shown). This is characteristic for CD-mediated monomeric lipid transfer (44), and therefore the labeled PE and PS species were most probably incorporated into cells (probably the exoplasmic leaflet of the plasma membrane) as lipid monomers rather than as components of adhering donor vesicles cf (45). Supporting this conclusion, only negligible amounts of the donor vesicle marker 22:0/22:0-PC, which is too hydrophobic to be efficiently transferred by cyclodextrins, was detected in cells (not shown).…”
Section: Cyclodextrin-mediated Introduction Of Aminophospholipidmentioning
confidence: 91%
“…The extent of this binding depends on the chain length and degree of saturation of the fatty acyl chains as well as on the CD cavity size (see (Huang and London, 2013)). It has been shown that the affinity of pyrene-labeled phospholipids for CDs increases with decreasing hydrophobicity (Tanhuanpää et al, 2001). For the experiments in buffer, additionally the organization of the analogs has to be taken into account, which depends on the fatty acyl chain length.…”
Section: Interaction Of Cds With Phospholipid Analogs In Aqueous Buffermentioning
confidence: 99%
“…Since fluorescence moieties are characterized by hydrophobic structures they may also bind to CDs (Kinsland and Wiechelman, 1984;Takakusa et al, 2001;Tanhuanpää et al, 2001;Fakayode et al, 2007). In this context, a carboxyethylated gCD has been shown to interact with various long chain fluorescently labeled phospholipids enhancing their translocation from lipid vesicles to cellular plasma membranes (Tanhuanpää and Somerharju, 1999;Tanhuanpää et al, 2001). The process of lipid extraction from membranes and the complexation of pyrene-labeled lipids by gCD were characterized in detail, indicating that the fluorescence moiety and both acyl chains of the analogs are bound to the same CD cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation